Nos trilhos da memória: a representação das ferrovias no imaginário sergipano - Oliveira, Bruno de Abreu (2021)
The railroad era began in 1830 when the first railway line for the transport of goods and passengers on a regular basis was inaugurated, between the cities of Liverpool and Manchester. In Brazil, the railway system started in the second half of the 19th century, stimulated by the Imperial Government. The train symbolized the embodiment of progress and development, in addition to being designated as a transmitter of civility. In the case of Sergipe, this was no different. That said, this research proposes to analyze the changes that remained vivid in the memory and in the railroad ideas of the people of Sergipe, between the years 1913-1979, a period of activity in passenger traffic. Initially, the first years of the railroads in Sergipe were evaluated, during the inauguration stages (1913-1915). In a second part, an analysis of the railway trajectory was carried out through the journalistic speeches between the years 1915 to 1950. And, lastly, we built a diagnosis of how the railway memory remains alive in Sergipe society, analyzing the traces left by the last years performance of Sergipe's locomotives in the decades of 50.60 and 70. Using tools such as reading and analyzing sources, such as Government Messages and periodicals, together with a bibliographic review on the theme and the use of Oral History, we will understand the imaginary and the railway memory existing in Sergipe.